A Balance Sheet Approach to Financial Crisis - Setser, Brad (IMF Working Papers; Working Paper, 2002)
The paper lays out an analytical framework for understanding crises in emerging markets based on examination of stock variables in the aggregate balance sheet of a country and the balance sheets of its main sectors (assets and liabilities). It focuses on the risks created by maturity, currency, and capital structure mismatches. This framework draws attention to the vulnerabilities created by debts among residents, particularly those denominated in foreign currency, and it helps to explain how problems in one sector can spill over into other sectors, eventually triggering an external balance of payments crisis. The paper also discusses the potential of macroeconomic policies and official intervention to mitigate the cost of such a crisis.